Predictors of mortality in immunocompromised children with respiratory infections - Lea Sutrisna; Rina Triasih; Ida Safitri Laksanawati (Paediatrica Indonesiana, 2022)
Background Respiratory infection is a common morbidity and a major cause of mortality in immunocompromised children. Hence, identification of clinical parameters that predict mortality among immunocompromised children with respiratory infections is of importance to provide timely and appropriate intervention. Objective To determine predictors of mortality in immunocompromised children with respiratory infections. Methods We conducted a prospective cohort study of immunocompromised children aged 18 years or younger with respiratory tract infections who were admitted to Dr. Sardjito Hospital, Yogyakarta, Indonesia. All eligible children were prospectively followed up until hospital discharge. Clinical and laboratory parameters during the first 24 hours of hospitalization were collected. Results Of 79 eligible children, the overall mortality was 11 subjects (13.9%). Fever, tachycardia, tachypnea, cyanosis, leukopenia, neutropenia, thrombocytopenia, and pleural effusion were predictive factors of mortality in bivariate analysis (P<0.25). A logistic regression model showed that neutropenia (absolute neutrophil count <125/mm3) and tachycardia were the best independent predictors of mortality in immunocompromised children with respiratory infections. The children with tachycardia had 15.8 times higher probability of mortality (95%CI 5.0 to 4.4) and those with neutropenia had 8.24 times higher probability of mortality. Cyanosis and pleural effusion were also independent mortality predictors. Conclusion The risk of mortality is significantly increased in immunocompromised children with respiratory infection when tachycardia and neutropenia are also present.